A performance management system for Manila Electric Company's (MERALCO) Corporate Information and Technology (CIT) Department The CIT Balanced Scorecard - Balaleng, Emma Ruth I. (University of the Philippines Diliman, 2010)
It is a given that one of the worst mistakes practitioners have seen made is for an organization to take measures that already exist, categorize them into four scorecard perspectives, and then announce that the scorecard had been built. These "metric" scorecards are of little value to an organization, as they bear little relationship to strategy, desired results and the processes needed to produce desired results. - Howard Rohm, Balanced Scorecard Institute. The reason as to why the above quote was stated in this section of this document is that it summarizes the mere existence of this project. Since 2005, the Corporate Information and Technology (CIT) department of the Manila Electric Company (MERALCO) has tried adopting the balanced scorecard concept. Though there are efforts started by the organization's key personnel to come up with a real scorecard, it seems that the developmental efforts of the BSC lacked other elements to make such efforts successful. Few versions (almost one version a year) of CIT's performance measurement systems were developed since 2005 to 2009 and all were named or titled as balanced scorecards. But the organization has not yet realized the genuine benefits of having an authentic BSC in place. This is because though certain elements towards the creation of the BSC already existed before, the more important ones were inexistent. Fortunately, these essential elements just came into existence just recently. And the organization's thrust to be continuously ISO 9001 : 2008 certified is the main driver for these new developments. From 2005 to 2009, Howard Rohm's above statement perfectly describes how the CIT tried or rather, half-heartedly tried to adopt the BSC. This project is a product of the CIT as it became more determined in implementing a better performance management system in place to help, not only the CIT management, but also the line personnel in making decisions and actions that will provide value to the entire company. Through the BSC, the CIT can be enabled to do the right things and to do things right. Based on business literatures, the balanced scorecard is a performance management system that can be used by any organization to align vision and mission with customer requirements, and day-to-day work, manage and evaluate business strategy, monitor operational efficiency improvements, build organization capacity, and communicate progress to all employees. The balanced scorecard allows the organization to measure financial and customer results, operations and organization capacity.